2019
DOI: 10.1111/hsc.12831
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of observational studies of adult home care

Abstract: The home‐care workforce is in high demand globally. Home‐care workers provide care for people at home, including practical and personal care, as well as other tasks such as medication management. We conducted a systematic review with the aims of understanding methods of observation that have been employed to study home care and to explore how these methods have enabled researchers to understand the quality of home care. We searched the literature using PubMed and CINAHL databases in May 2018, with no limits ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Homecare for people living with dementia should continue to be explored through inclusive methods of data collection. Our study, in addition to previous research [ 16 ], found ethnographic participant observations were well-suited to capturing the lived-experiences of people living with dementia, including people who lack decision-making capacity, in the private setting of their home. Participant observations of care delivered in the home highlighted important considerations about the home environment itself and the way homecare workers interact with the home.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Homecare for people living with dementia should continue to be explored through inclusive methods of data collection. Our study, in addition to previous research [ 16 ], found ethnographic participant observations were well-suited to capturing the lived-experiences of people living with dementia, including people who lack decision-making capacity, in the private setting of their home. Participant observations of care delivered in the home highlighted important considerations about the home environment itself and the way homecare workers interact with the home.…”
Section: Discussionmentioning
confidence: 85%
“…The participant observations were guided by our earlier methodological review of observational studies of homecare [ 16 ]. Three researcher-observers (ML, AB and JBD) from psychology and sociology backgrounds conducted naturalistic observations of homecare workers, guided by a semi-structured observation guide ( Appendix B ) intended to enhance consistency of fieldnotes across observers and prompt reflexivity.…”
Section: Methodsmentioning
confidence: 99%
“…29 The balancing of roles is complex for carers especially involving boundaries between advocating for independence and the implementation of medical advice. 30 Our findings demonstrate this dilemma extends to the management of long-term conditions in dementia. Future research is required to understand how calculated risks in care decision-making can enable freedom for people with dementia while managing carer safety concerns.…”
Section: Main Findingsmentioning
confidence: 69%
“…In addition to participant feedback, observation was used to examine and evaluate the different techniques. Observation is an established and valuable method for examining and evaluating practices, services, and behaviors [38][39][40]. For example, in education, peer observation and critical self-reflection are employed to evaluate teaching technique and student engagement [41,42], while, in health research, observation is used to assess diverse items such as nature-based therapeutic interventions [43], dementia care and dementia care services in different settings [39,44,45], and the allocation of pre-hospital medical assistance and resources [46].…”
Section: Methodsmentioning
confidence: 99%